2018
DOI: 10.1115/1.4038944
|View full text |Cite
|
Sign up to set email alerts
|

Selective Band Gap to Suppress the Spurious Acoustic Mode in Film Bulk Acoustic Resonator Structures

Abstract: In this work, we investigate numerically the propagation of Lamb waves in a film bulk acoustic resonator (FBAR) structure formed by piezoelectric ZnO layer sandwiched between two Mo electrodes coupled with Bragg reflectors; the system is thus considered as a phononic-crystal (PnC) plate. The aim is to suppress the first-order symmetric Lamb wave mode considered as a spurious mode caused by the establishment of a lateral standing wave due to the reflection at the embedded lateral extremities of the structure; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…By adding the PnC structure, a bandgap can be formed on the dispersion curve, and the spurious mode in the bandgap is prohibited ( Figure 13 ). Generally, the position of the bandgap can be adjusted be close to the main resonance frequency by controlling the structural size of the PnC [ 93 ].…”
Section: Spurious Modementioning
confidence: 99%
See 2 more Smart Citations
“…By adding the PnC structure, a bandgap can be formed on the dispersion curve, and the spurious mode in the bandgap is prohibited ( Figure 13 ). Generally, the position of the bandgap can be adjusted be close to the main resonance frequency by controlling the structural size of the PnC [ 93 ].…”
Section: Spurious Modementioning
confidence: 99%
“… ( a ) Dispersion curve of acoustic waves in the FBAR; the formation of PnC directly bans the TE1 spurious mode generation at the antiresonance frequency [ 93 ]. ( b ) Comparison between the calculated input admittances of FBAR without PnC and with PnC.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [6 ] reported that a transverse‐free fundamental resonance is obtained provided that period of grating and thickness is set so that the stop band covers the range of frequencies where the transverse mode resonances occur. This technique is effective to suppress the transverse resonances and improve the quality factor at the cost of reducing the effective electromechanical coupling coefficient [7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent these difficulties, filters and wave guides had previously been developed to isolate specific modes of the Lamb wave [6,7], as well as to confine the wave propagation to specific directions [8]. The strategies for mode isolation revolve mainly around the use of phononic crystals, which prevents the transmission of selective wave frequencies through the action of Bragg scattering [9][10][11][12][13][14][15][16][17][18][19][20][21]. To achieve unidirectional transmission, on the other hand, requires breaking either the spatial inversion symmetry or the time-reversal symmetry [22].…”
Section: Introductionmentioning
confidence: 99%